1989
DOI: 10.1128/jb.171.11.6069-6076.1989
|View full text |Cite
|
Sign up to set email alerts
|

The 5'-flanking region of the gene encoding the large subunit of ribulose-1,5-bisphosphate carboxylase/oxygenase is crucial for growth of the cyanobacterium Synechococcus sp. strain PCC 7942 at the level of CO2 in air

Abstract: Transformation of the high-CO2-requiring mutants (hcr) 0221 and El derived from the cyanobacterium Synechococcus sp. strain PCC 7942 by a wild-type DNA library restored their ability to grow at the level of CO2 in air. A plasmid (pE12) containing a 10-kilobase DNA insert was rescued from a 0221 heterogenote and proved to transform both 0221 and El to the wild-type phenotype. The capacity of the pE12 subclones to confer the wild-type phenotype to 0221 transformants enabled the mapping of the mutation in 0221 (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
2

Year Published

1990
1990
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 31 publications
4
64
2
Order By: Relevance
“…Such mutants would be expected to exhibit normal photosynthetic performance under high-CO2 conditions (including apparent photosynthetic affinity for CQ), but would fail to adapt and grow under low CO2. This behavior contrasts with that of other types of high-C02-requiring mutants defective in the ability to utilize the internal C1 pool, which exhibit very low apparent photosynthetic affinity to C1 (8) . The level of some of the transcripts originating from this region (including that from rbc) depends on the CO2 concentration during growth.…”
Section: The Nature Of the Signal For Adaptation To Low C02 Concentracontrasting
confidence: 43%
“…Such mutants would be expected to exhibit normal photosynthetic performance under high-CO2 conditions (including apparent photosynthetic affinity for CQ), but would fail to adapt and grow under low CO2. This behavior contrasts with that of other types of high-C02-requiring mutants defective in the ability to utilize the internal C1 pool, which exhibit very low apparent photosynthetic affinity to C1 (8) . The level of some of the transcripts originating from this region (including that from rbc) depends on the CO2 concentration during growth.…”
Section: The Nature Of the Signal For Adaptation To Low C02 Concentracontrasting
confidence: 43%
“…It would be expected that immature stages appear during this period of active assembly of new carboxysomes. We have also observed carboxysomes with an electron-translucent area (type C) in Anabaena cells grown under severe limitation of Q induced by Na + deficiency (E. FernandezValiente, personal communication), in Synechococcus (Friedberg et al, 1989;Kaplan, 1990), and in Synechocystis (Ogawa et al, 1994), although such structures had not been pointed out by the various authors cited.…”
Section: Carboxysome Maturation Stagesmentioning
confidence: 87%
“…Such increased synthesis of carboxysome precursors might result in their assembly into the bar-shaped carboxysomes frequently found in this mutant. Bar-shaped carboxysomes have been reported in HCRM type I and PVU (Price and Badger, 1991) and E1 (Friedberg et al, 1989) and have been interpreted as aberrant bodies resulting from the alteration of ccmL. However, this type of carboxysome coexists with typical carboxysomes in the same cell and have also been found in wildtype Synechococcus under conditions of predictable severe stress for C , such as stationary-phase old cultures (Gantt and Conti, 1969) and cultures bubbled with 30 pL of CO, in air at pH 9.5 (McKay et al, 1993).…”
Section: Carboxysomes Of Hcrmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutants of similar phenotype have been isolated from Synechococcus PCC7942 (1, 11, 14, 21, 23). Molecular analysis of two of these mutants of Synechococcus, 022, and E1, revealed that the sites of mutations are on the 5'-flanking region of the gene encoding the large subunit of ribulose-1 ,5-bisphosphate carboxylase/oxygenase (8). Price and Badger (21) (Fig.…”
Section: Discussionmentioning
confidence: 99%